1997
DOI: 10.1093/ndt/12.6.1262
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in the haemoglobin level in haemodialysis patients undergoing antiandrogen therapy

Abstract: rolide; haemoglobin Three Caucasian haemodialysis patients were diagnosed with prostatic cancer. The clinical and biochemical data at the time of diagnosis are shown in Table 1. During the 12 months prior to diagnosis, stable haemoglobin levels were maintained with monthly doses of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…We first tested whether testosterone had an influence on Epo transcription in the liver and/or the kidney but did not find a significant difference in Epo mRNA levels between Bmp6 −/− males and females (data not shown). In humans, levels of erythropoietin are also similar in men and women and it is assumed that testosterone increases the sensitivity of erythroid progenitors to erythropoietin . To test whether the down‐regulation of hepcidin expression by testosterone in Bmp6 −/− mice was due to the stimulation of erythropoiesis, we irradiated ovariectomized females ( 60 Co, 6Gy) to inhibit erythropoiesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first tested whether testosterone had an influence on Epo transcription in the liver and/or the kidney but did not find a significant difference in Epo mRNA levels between Bmp6 −/− males and females (data not shown). In humans, levels of erythropoietin are also similar in men and women and it is assumed that testosterone increases the sensitivity of erythroid progenitors to erythropoietin . To test whether the down‐regulation of hepcidin expression by testosterone in Bmp6 −/− mice was due to the stimulation of erythropoiesis, we irradiated ovariectomized females ( 60 Co, 6Gy) to inhibit erythropoiesis.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, levels of erythropoietin are also similar in men and women and it is assumed that testosterone increases the sensitivity of erythroid progenitors to erythropoietin. 20 To test whether the down-regulation of hepcidin expression by testosterone in Bmp6 2/2 mice was due to the stimulation of erythropoiesis, we irradiated ovariectomized females ( 60 Co, 6Gy) to inhibit erythropoiesis. Testosterone propionate (10 mg/kg) or vehicle was then administered on days 2 to 8.…”
Section: Resultsmentioning
confidence: 99%
“…Some reports suggested that the adjustment in patients with renal insufficiency was not required. In contrast, Teruel et al reported serious side effects of CAB therapy in hemodialysis patients under normal dose usage 13 . In the present case, we started at two‐thirds usual dosage of flutamide and ordinary use of LHRH analogue.…”
Section: Discussionmentioning
confidence: 52%
“…In contrast, Teruel et al reported serious side effects of CAB therapy in hemodialysis patients under normal dose usage. 13 In the present case, we started at two-thirds usual dosage of flutamide and ordinary use of LHRH analogue. Fortunately, and as expected, CAB therapy was very effective and this may be the first report to have treated prostate cancer with multiple lung metastases in a hemodialysis patient.…”
Section: Discussionmentioning
confidence: 82%
“…Some reports of prostate cancer in chronic hemodialysis patients have been published recently and the efficacy and pharmacokinetics of LH-RH agonists in these patients have been noted. [5][6][7][8][9] Oelschläger et al found no remarkable differences in serum fosfestrol and DES concentrations between prostate cancer patients with a 50% reduction in creatinine clearance and those with normal renal function. 11 In this case, patients received 1500 mg of fosfestrol by drip infusion over 3.5 h. Fosfestrol is metabolized to DES by phosphatase mainly in the liver and DES is eliminated into urine or feces after being conjugated by glucuronide or sulfate in the liver.…”
Section: Discussionmentioning
confidence: 99%